2005
DOI: 10.1111/j.1467-8691.2005.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Innovative Work Behaviour: Development and Test of an Integrated Model

Abstract: In this study, we developed and tested a causal model to predict innovative work behaviour (IWB) integrating the literatures on psychological contract, job design and organizational justice. Two hundred and four employees from Irish manufacturing organizations participated in the study, and we collected data using a survey questionnaire. The psychological contract variable of perceived obligation to innovate, job autonomy and pay showed direct effects on IWB. In addition, pay and job autonomy also had indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
360
1
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(392 citation statements)
references
References 13 publications
20
360
1
11
Order By: Relevance
“…Employees who engage in innovative behavior develop ideas that would otherwise not be developed, and then carry, react to, and modify these ideas. Thus, employees are crucial when innovating products, processes, and methods within an organization (Ramamoorthy et al, 2005).…”
Section: Innovative Work Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Employees who engage in innovative behavior develop ideas that would otherwise not be developed, and then carry, react to, and modify these ideas. Thus, employees are crucial when innovating products, processes, and methods within an organization (Ramamoorthy et al, 2005).…”
Section: Innovative Work Behaviormentioning
confidence: 99%
“…In today's competitive and rapidly changing environment, organizations face increasing pressure to engage in innovative behaviors in order to create and deliver new products and gain a sustainable competitive advantage. Consequently, organizations are increasingly relying on their employees to be innovative (Ramamoorthy et al, 2005). For instance, Getz and Robinson (2003) found that employees initiated 80 percent of the ideas in one organization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ramamoorthy et al (2005) found that the organisational process of meritocracy, equity perceptions and procedural justice perceptions influenced innovative work behaviour.…”
Section: Communication and Collaboration Processesmentioning
confidence: 99%
“…They also identified the importance of providing the job incumbent with autonomy in decision making about how they undertook the role. Support for the provision of adequate autonomy on a creative work environment has also been provided by Ramamoorthy et al (2005).…”
Section: The Influence Of Job Design Factors On the Work Environmentmentioning
confidence: 99%
“…Employee innovation is needed in terms of products, processes, methods and also in operational activities (Ramamoorthy et al, 2005). Innovative work behavior becomes necessary close to the workers daily activities for the organizational benefit (e.g.…”
Section: Introductionmentioning
confidence: 99%